Two weeks of pretreatment with escitalopram facilitates extinction learning in healthy individuals. (15th June 2013) - Bui, Eric; Orr, Scott P.; Jacoby, Ryan J.; Keshaviah, Aparna; LeBlanc, Nicole J.; Milad, Mohammed R.; Pollack, Mark H.; Simon, Naomi M.
Abstract : Objective: We aimed to examine whether pretreatment with escitalopram would be associated with reduced fear acquisition and enhanced extinction learning in a fear conditioning paradigm, compared with placebo. Methods: Healthy volunteers were randomized in double‐blind fashion, to 14 days of escitalopram 10 mg/day ( n  = 18) or placebo ( n  = 20) prior to a classical fear conditioning paradigm. Results: Although escitalopram was associated with a smaller skin conductance (SC) orienting response during habituation, no medication effects on fear acquisition were found. Escitalopram was associated with faster extinction of SC responses, compared with placebo, as revealed by a significant drug × conditioned stimulus × trial interaction for early extinction ( F (3, 30) = 3.26, p  = 0.035) and late extinction ( F (3, 30) = 3.27, p  = 0.035) trials. After adjustment for age, orienting response, and acquisition, results from linear contrast remained significant for early extinction ( F (1, 29) = 5.43, p  = 0.027). Conclusions: Escitalopram administered for 14 days prior to a fear conditioning paradigm did not influence acquisition of a conditioned fear response but did facilitate extinction learning. Impairments in extinction learning have been identified as a key component of posttraumatic stress disorder; our preliminary findings suggest that additional experimental and clinical studies assessing the efficacy of selective serotonin reuptake inhibitors for posttraumatic stress disorder prevention are warranted. Copyright © 2013 John Wiley & Sons, Ltd.